The impact of networking among women entrepreneurial success / Shamsul Hana Abd Rani…[et al.] - Abd Rani, Shamsul Hana; Hashim, Norashidah; Abd Rani, Shamsul Huda (Universiti Teknologi MARA, Kedah, 2019)
The success among entrepreneurs are said to be influence by many factors which is one of the main contribution is their networking. Networking play a major role in determining how far the business can expand. Women entrepreneurs are usually considered nearby friends and family in their circle of network. Thus, the study would examine either the networking gives impact to the success among women entrepreneurs in Malaysia. The result revealed that networking is very important to help women expand their business. Besides, through networking, women entrepreneur also gained so much benefits in terms of entrepreneurial activities such as learned skills and also support from people surround them. Therefore, the study results are significant to guide researchers with hope that it will enhance their understanding on the important of having good network in order to become a successful entrepreneur